Effect of Diversification, Good Corporate Governance, Corporate Social Responsibility on Business Risk (Study on Manufacturing Companies listed on the Stock Exchange I 2015-2019) - Habibie, Surya (International Journal of Economic, Business & Applications, 2022)
This study aims to analyze the effect of Diversification, Good Corporate Governance, Corporate Social Responsibility on Company Risk. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period, which amounted to 176 companies. The research method used in this research is the explanatory method which aims to test the effect between variables through hypothesis testing using quantitative data. This study uses secondary data obtained from the website www.idx.co.id and the company's Annual Report. The sample selection used purposive sampling method with a total of 205 data from 41 companies in each period. This study uses Structural Equation Modeling-Partial Least Square (SEM-PLS) in analyzing the data. The results showed that Diversification had a positive and significant effect on Corporate Risk, Good Corporate Governance had a positive and significant impact on Corporate Risk, and Corporate Social Responsibility had a positive and significant impact on Corporate Risk. Company risk in this study is measured using Business Risk. Diversification is measured using the Herfindahl index, Good Corporate Governance is measured by the KNKG standard, and Corporate Social Responsibility is measured using the GRI-G4 indicator with the formula Good Corporate Governance has a positive and significant effect on Company Risk, Corporate Social Responsibility has a positive and significant impact on Company Risk. Company risk in this study is measured using Business Risk. Diversification is measured using the Herfindahl index, Good Corporate Governance is measured by the KNKG standard, and Corporate Social Responsibility is measured using the GRI-G4 indicator with the formula Good Corporate Governance has a positive and significant effect on Company Risk, Corporate Social Responsibility has a positive and significant impact on Company Risk . The company's risk in this study is measured using Business Risk. Diversification is measured using the Herfindahl index, Good Corporate Governance is measured by the KNKG standard, and Corporate Social Responsibility is measured using the GRI-G4 indicator with the formula Corporate Social Responsibility has a positive and significant impact on Company Risk. The company's risk in this study is measured using Business Risk. Diversification is measured using the Herfindahl index, Good Corporate Governance is measured by the KNKG standard, and Corporate Social Responsibility is measured using the GRI-G4 indicator with the formula Corporate Social Responsibility has a positive and significant impact on Company Risk. The company's risk in this study is measured using Business Risk. Diversification is measured using the Herfindahl index, Good Corporate Governance is measured by the KNKG standard, and Corporate Social Responsibility is measured using the GRI-G4 indicator with the formula CSR disclosure ratio measurement